Comenius and the Low Countries : Some Aspects of Life and Work of a Czech Exile in the Seventeenth Century - Rood, Wilhelmus, (European History and Culture - Book Archive pre-2000., 1970)
This study follows Comenius' life in Holland and analyses the contacts with his contemporaries, adding quite an amount of unknown facts to the knowledge about this important scholar and pedagogue.